Establishing and prioritizing research questions for the treatment of alopecia areata: the Alopecia Areata Priority Setting Partnership. (1st May 2017) - Macbeth, A.E.; Tomlinson, J.; Messenger, A.G.; Moore‐Millar, K.; Michaelides, C.; Shipman, A.R.; Kassim, J.M.; Brockley, J.R.; Szczecinska, W.; Farrant, P.; Robinson, R.; Rodgers, J.; et al.
Summary: Background: Alopecia areata (AA) is a common hair loss disorder that results in patchy to complete hair loss. Many uncertainties exist around the most effective treatments for this condition. Objectives: To identify uncertainties in AA management and treatment that are important to both service users (people with hair loss, carers and relatives) and healthcare professionals. Methods: An AA priority setting partnership was established between patients, their carers and relatives, and healthcare professionals to identify the most important uncertainties in AA. The methodology of the James Lind Alliance was followed to ensure a balanced, inclusive and transparent process. Results: In total, 2747 treatment uncertainties were submitted by 912 participants, of which 1012 uncertainties relating to AA (and variants) were analysed. Questions were combined into 'indicative uncertainties' following a structured format. A series of ranking exercises further reduced this list to a top 25 that were taken to a final prioritization workshop where the top 10 priorities were agreed. Conclusions: We present the top 10 research priorities for AA to guide researchers and funding bodies to support studies important to both patients and clinicians.